2022
DOI: 10.1080/10717544.2022.2100515
|View full text |Cite
|
Sign up to set email alerts
|

Optimized self-microemulsifying drug delivery system improves the oral bioavailability and brain delivery of coenzyme Q10

Abstract: Our study aimed to develop a self-microemulsifying drug delivery system for the poorly aqueous-soluble drug Coenzyme Q 10 , to improve the dissolution and the oral bioavailability. Excipients were selected based on their Coenzyme Q 10 solubility, and their concentrations were set for the optimization of the microemulsion by using a D-optimal mixture design to achieve a minimum droplet size and a maximum solubility of Coenzyme Q 10 within 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
6
0
1
Order By: Relevance
“…The nanoparticles exhibited a high accumulation in SCC7 tumor tissue in rats after intravenous injection (Figure 16). The bioavailability of coenzyme Q 10 loaded by the SMEDDS was also improved as compared to coenzyme Q 10 unloaded by the SMEDDS [32]. The concentration of coenzyme Q 10 in blood when administrated with coenzyme Q 10 SMEDDS was much higher than that when administrated with coenzyme Q 10 suspension (Figure 17).…”
Section: Rhamnolipid-coatedmentioning
confidence: 98%
See 1 more Smart Citation
“…The nanoparticles exhibited a high accumulation in SCC7 tumor tissue in rats after intravenous injection (Figure 16). The bioavailability of coenzyme Q 10 loaded by the SMEDDS was also improved as compared to coenzyme Q 10 unloaded by the SMEDDS [32]. The concentration of coenzyme Q 10 in blood when administrated with coenzyme Q 10 SMEDDS was much higher than that when administrated with coenzyme Q 10 suspension (Figure 17).…”
Section: Rhamnolipid-coatedmentioning
confidence: 98%
“…Thapa Chhitij et al have optimized the conditions for the preparation of SMEDDS containing coenzyme Q 10 [32]. By D-optimal mixture design, the authors found the optimal formulation for SMEDDS based on the solubility and concentration of these systems.…”
Section: Sample Vibration (Cmmentioning
confidence: 99%
“…These findings suggested that in primary coenzyme Q10 deficiency, CoQ10 distribution in the brain may be improved by the administration of LDLR inhibitors or by interventions to stimulate the luminal activity of SR-B1 transporters [ 60 ]. Better CoQ10 brain distribution and peak plasma concentration were achieved in rat models using a self-microemulsifying drug delivery system of CoQ10 compared to the coenzyme Q10 suspension [ 61 ]. Sheykhhasan et al reported a positive effect of CoQ10 drug delivery with the use of exosomes derived from adipose-derived stem cells (ADSCs-Exo) in a rat model of Alzheimer’s disease [ 62 ].…”
Section: Primary Coenzyme Q10 Deficiency-4mentioning
confidence: 99%
“…Q10 bioaccessibilities were also found as 63.75 ± 0.91 and 46.83 ± 1.27% in yogurts enriched with emulsified Q10, and γ-cyclodextrin/Q10 complex, respectively. Consequently, to overcome the drawbacks of Q10 and expand its applications to relevant fields, researchers are developing different strategies to overcome these challenges, including encapsulating the Q10 in delivery systems, such as nanoemulsions, nanoparticles, microparticles, liposomes, and cyclodextrins. , In this study, we focused on the utilization of oil-in-water (O/W) nanoemulsions to encapsulate Q10.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, to overcome the drawbacks of Q10 and expand its applications to relevant fields, researchers are developing different strategies to overcome these challenges, including encapsulating the Q10 in delivery systems, such as nanoemulsions, nanoparticles, microparticles, liposomes, and cyclodextrins. 16,17 In this study, we focused on the utilization of oil-in-water (O/W) nanoemulsions to encapsulate Q10. Oil-in-water nanoemulsions are usually prepared by homogenizing an oil phase with a water phase containing a suitable emulsifier.…”
Section: Introductionmentioning
confidence: 99%